Marine ecosystem community carbon and nutrient uptake stoichiometry under varying ocean acidification during the PeECE III experiment - R. G. J. Bellerby; K. G. Schulz; U. Riebesell; C. Neill; G. Nondal; E. Heegaard; T. Johannessen; K. R. Brown (Biogeosciences, 2008)
Changes to seawater inorganic carbon and nutrient concentrations in response to the deliberate CO2 perturbation of natural plankton assemblages were studied during the 2005 Pelagic Ecosystem CO2 Enrichment (PeECE III) experiment. Inverse analysis of the temporal inorganic carbon dioxide system and nutrient variations was used to determine the net community stoichiometric uptake characteristics of a natural pelagic ecosystem perturbed over a range of pCO2 scenarios (350, 700 and 1050 μatm). Nutrient uptake showed no sensitivity to CO2 treatment. There was enhanced carbon production relative to nutrient consumption in the higher CO2 treatments which was positively correlated with the initial CO2 concentration. There was no significant calcification response to changing CO2 in Emiliania huxleyi by the peak of the bloom and all treatments exhibited low particulate inorganic carbon production (~15 μmol kg−1). With insignificant air-sea CO2 exchange across the treatments, the enhanced carbon uptake was due to increase organic carbon production. The inferred cumulative C:N:P stoichiometry of organic production increased with CO2 treatment from 1:6.3:121 to 1:7.1:144 to 1:8.25:168 at the height of the bloom. This study discusses how ocean acidification may incur modification to the stoichiometry of pelagic production and have consequences for ocean biogeochemical cycling.